2021
DOI: 10.4103/jehp.jehp_771_20
|View full text |Cite
|
Sign up to set email alerts
|

Entry level nursing graduate students’ perception and readiness toward online component of blended learning

Abstract: BACKGROUND: Blended learning (BL), the integration of online with face to face teaching, is established as a teaching method in higher education. Understanding the learner's readiness toward online component of BL is important in designing and delivering BL. Nursing students require proficiency in interpersonal relationship and social interaction apart from knowledge and skills. BL may provide an opportunity to acquire the professional skills better than the traditional face to face sessions. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[ 32 ] A focus group discussion among health sciences students revealed that online learning/e-learning gives them the flexibility of learning time and enables slow learners to repeatedly learn/view and understand the contents without having anxiousness of absenteeism. [ 33 34 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32 ] A focus group discussion among health sciences students revealed that online learning/e-learning gives them the flexibility of learning time and enables slow learners to repeatedly learn/view and understand the contents without having anxiousness of absenteeism. [ 33 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…WhatsApp-based e-learning for radiodiagnosis of clinical diagnosis among Italian and Indian dental professionals revealed an effective method for diagnosis and treatment planning among students and personnel working in remote community camps. [ 30 31 32 33 34 35 ] Almost entire (98.6%) of dental students found the correct interpretation of dental radiographs than their control group taught by conventional methods. [ 36 ] Sarode, in his work on community surveys, declared that WhatsApp-based second opinion diagnosis is an efficient method to overcome the problem of diagnostic delays in oral cancer screening.…”
Section: Introductionmentioning
confidence: 99%